THE INFLUENCE OF ACCOUNTING UNDERSTANDING AND APPLICATION OF REGIONAL FINANCIAL INFORMATION SYSTEMS ON QUALITY OF LOCAL GOVERNMENT FINANCIAL REPORT WITH HUMAN RESOURCE COMPETENCIES AS MODERATING VARIABLE: EMPIRICAL STUDY OF THE GOVERMENT PEKANBARU CITY - Andri, Andri (International Journal of Business and Information Technology, 2021)
This study aims to determine the influence of Accounting Understanding an Application, financial accounting systems human resource competency on the quality of regional financial statement. Based on PP No. 71 year 2010, state and local government financial statement quality have to meet the qualitative characteristic. Factors examined include Acounting understanding, human resource competency financial accounting system and the quality of regional financial statement. The used sampling method is purposive sampling sampling. Data collection is done by giving as many as 90 copies, copies of the questionnaire,which was distributed to respondents who are staff financial in Pekanbaru City. The Data obtained are then analyzed using SPSS 21.00. Based on the analysis results, obtained that applicatin of Accounting and the financial accounting systems have a positive and significant effect to the quality of financial reporting information in OPD Pekanbaru City and human resource competency can be used as a moderating variable